The male sex pheromone darcin stimulates hippocampal neurogenesis and cell proliferation in the subventricular zone in female mice - Hoffman, Emma; Pickavance, Lucy; Thippeswamy, Thimmasettappa; Beynon, Robert J.; Hurst, Jane L. (Frontiers in Behavioral Neuroscience, 2015)
The integration of newly generated neurons persists throughout life in the mammalian olfactory bulb and hippocampus, regions involved in olfactory and spatial learning. Social cues can be potent stimuli for increasing adult neurogenesis; for example, odors from dominant but not subordinate male mice increase neurogenesis in both brain regions of adult females. However, little is known about the role of neurogenesis in social recognition or the assessment of potential mates. Dominant male mice scent-mark territories using urine that contains a number of pheromones including darcin (MUP20), a male-specific major urinary protein that stimulates rapid learned attraction to the spatial location and individual odor signature of the scent owner. Here we investigate whether exposure to darcin stimulates neurogenesis in the female brain. Hippocampal neurons and cellular proliferation in the lateral ventricles that supply neurons to the olfactory bulbs increased in females exposed for seven days to male urine containing at least 0.5µg/µl darcin. Darcin was effective whether presented alone or in the context of male urine, but other information in male urine appeared to modulate the proliferative response. When exposed to urine from wild male mice, hippocampal proliferation increased only if urine was from the same individual over seven days, suggesting that consistency of individual scent signatures is important. While seven days exposure to male scent initiated the first stages of increased neurogenesis, this caused no immediate increase in female attraction to the scent or in the strength or robustness of spatial learning in short-term conditioned place preference tests. The reliable and consistent stimulation of neurogenesis by a pheromone important in rapid social learning suggests that this may provide an excellent model to explore the relationship between the integration of new neurons and plasticity in spatial and olfactory learning in a socially-relevant context.